Rethinking Early Homeopaths: When and Why to Use Pathognomonic Symptoms - Grühn, Monika (Homœopathic Links, 2014)
For improving our results, we may need to use pathognomonic symptoms; yet, it is often said we should avoid them. But early homeopaths like Georg Heinrich Gottlieb Jahr and Constantine Hering advised us to also consider them in case analysis. Rethinking relevant passages of their writings as well as of Carroll Dunham throws light on how early homeopaths, Samuel Hahnemann included, considered pathognomonic symptoms, namely as being part of a symptom totality. This, in turn, explains why Heiner Frei got better results in an investigation with ADHD patients, by using the currently existing pathognomonic symptoms. Such data suggest that we can thus improve our results in daily practice. In this part 1, we will especially consider various texts of Jahr. They are among the first texts ever in homeopathic literature, where a division of symptoms into those of the “patient” and those of a “disease” was made. Jahr tells us why he developed such explanations, and what he meant by them. Then Hering, from a partly different point of view, explains which pathognomonic symptoms can be among the characteristic symptoms.
Keywords: Jahr; Hering; Patient; Disease; Pathognomonic; Characteristic; Individual; Symptom totality